Cardiovascular risk and blood pressure lowering treatment among elderly individuals: Evidence for Cardiovascular Prevention from Observational Cohorts in Japan. Issue 2 (February 2018) - Asayama, Kei; Ohkubo, Takayoshi; Satoh, Atsushi; Tanaka, Sachiko; Higashiyama, Aya; Murakami, Yoshitaka; Yamada, Michiko; Saitoh, Shigeyuki; Okayama, Akira; Miura, Katsuyuki; Ueshima, Hirotsugu; Miyamoto, Yoshihiro; et al.
Abstract : Objective: There is little evidence to support an increased risk of blood pressure (BP) elevation among elderly individuals receiving antihypertensive drug treatment. Methods: To clarify the impact on BP level and residual cardiovascular risk in treated elderly individuals, we analysed individual participant data of 26 133 residents aged 60–89 years from seven Japanese general populations and cross-classified participants by age category, 60–74 (young-old) versus 75–89 years (old-old), and by usage of antihypertensive medication at baseline survey (1980–1995). Results: During a median follow-up period of 12.7 years, 2451 cardiovascular deaths were observed. Multivariable-adjusted hazard ratios of cardiovascular mortality in treated participants compared with untreated participants were 1.30 [95% confidence intervals, 1.16–1.46) and 1.35 (95% confidence interval, 1.16–1.56) in young-old and old-old participants, respectively. Irrespective of antihypertensive medication, the risk increase of total cardiovascular and stroke mortality with elevation of BP was significant among young-old ( P  ⩽ 0.0013), but not significant among old-old participants ( P  ≥ 0.061). Conclusion: Although impact on BP was more evident among young-old than old-old individuals, clinicians who prescribe antihypertensive medication to elderly patients should consider that such patients require further monitoring. Abstract : Supplemental Digital Content is available in the text